Synthesis of Fibrin Clot from Fibrinogen Platelet Rich Plasma (PRP) for Scaffold Applications - Rahman, Siti Fauziyah (Universitas Indonesia, 2023)
Platelet-rich plasma (PRP), which contains fibrinogen, is activated by the addition of thrombin and calcium chloride to create fibrin clots. Fibrin is a natural biopolymer that can be applied for medical applications. This study aims to synthesize fibrin clots from fibrinogen platelet-rich plasma for scaffold applications. The optimum amount of fibrin clot can be obtained by varying the ratio of PRP to a mixture of CaCl2 with the variation of 9:1, 10:1, and 11:1. The highest fibrin clot produced was 5.925 ml with 5.5% CaCl2.